Analysis of Changes in the Procurement Process in a Transport Company Caused by Implementation of Digital Twin - Yekaterina Kovaleva (Global Journals of Research in Engineering, 2021)
This article illustrates the changes in the process of purchasing parts and components in a railway company when implementing a smart asset management system. The processes built in BPMN notation illustrate the flow of work that is understandable for people with different backgrounds. When analyzing the process as it is, the company's weaknesses were identified, which justified the need to introduce new technologies. In the modern world, there are many solutions for asset management automation. During the analysis, it was decided that the company needs a new information system supported by the constant collection of data from smart sensors. Such a system is a digital twin of vehicles, which makes it possible to predict future changes and make timely decisions. To demonstrate the improvements that the company can get, the processes were built as they should be, and conclusions were drawn on what positive effect the implementation of the new system will have.